Effects of Sedation Depth on Mechanical Ventilation, Delirium, and Recovery: A Systematic Review - Anna Millizia; Mumya Camary; Muhammad Bayu Rizaldy; Yuziani (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2026)
Sedation is an essential component of intensive care unit (ICU) management; however, excessive sedation may adversely affect clinical outcomes. This systematic review evaluated the association between sedation depth and clinical outcomes in adult ICU patients receiving mechanical ventilation. A literature search was conducted according to PRISMA 2020 guidelines using PubMed, Scopus, Web of Science, and Google Scholar. Studies published between 2010 and 2023 assessing sedation depth with validated instruments in mechanically ventilated adults were included. Twelve studies involving more than 7,000 patients met the inclusion criteria. Most studies reported that deep sedation, particularly during the first 48 hours of ICU admission, was associated with higher mortality, prolonged mechanical ventilation, increased delirium incidence, and poorer long-term cognitive and functional outcomes. In contrast, light sedation strategies combined with regular assessment, sedation interruption, and multimodal analgesia were associated with reduced delirium risk, shorter ventilation duration, and improved recovery. Current evidence suggests that sedation depth significantly influences outcomes in critically ill patients. Light sedation should be considered whenever clinically appropriate, while further studies are needed to evaluate long-term recovery and develop individualized sedation approaches.